Uji Isolat Bakteri Azotobacter Asal Kebun Lidah Buaya dengan Pupuk Urea terhadap Serapan Nitrogen pada Tanaman Kedelai (Glycine Max L.) di Tanah Gambut - Erlanda, Nandung; Arief, Feira B.; Umran, Ismahan; Gafur, Sutarman; Suswati, Denah (Proceedings Series on Physical & Formal Sciences, 2021)
Azotobacter nitrogen-fixing bacteria and urea fertilizer to reduce excessive use of chemical fertilizers. These bacteria can play a role in increasing nitrogen uptake and further growth of soybean plants. This study aimed to obtain growth media for Azotobacter and increase plant and root growth and nitrogen uptake of Biosoy soybean varieties. The research was conducted to help the uptake of n in the soil and reduce the excessive use of chemical fertilizers. The first experiment was carried out by growing bacteria on the media for 120 hours. The second experiment was designed in a completely randomized design that tested two treatments with additional use of urea fertilizer and Azotobacter and no Azotobacter. The results showed that there was no effect of giving Azotobacter from aloe vera gardens, and urea fertilizer showed a significant effect on the observed variables of soil pH in soybean plants on peat soil. In contrast, the variables observed were population, plant height, N content, N-total, plant dry weight, dry weight of plant roots, and N span of soybean plants had no significant effect.